Integration of Islamic Education in Strengthening Students’ Values of Moderation in Modern Society - Fadilla Syahriani; Nadyya Zahratul Jannah (Modern Islamic Studies and Sharia Research, 2025)
This study aims to analyse the role of integration ofIslamic education in strengthening the moderation values of students in modern society that is characterised by technological development, globalisation, andmodern society characterised by technological development, globalisation, and social and cultural change.social and cultural changes. This research uses a qualitative approachapproach with field research method. Data were collected throughobservation, in-depth interviews, and documentation in several Islamic educational institutions that implement moderation values in the learning process.Islamic educational institutions that apply moderation values in the learning process. The analysis ofdata was analysed descriptively-analytically to understand the implementation of the integration of IslamicIslamic education integration implementation in shaping students' moderate character. The resultsThe results showed that the integration of Islamic education values inteaching and learning activities plays an important role in fostering an attitude of tolerance,justice, and balance among students. The values of religious moderationvalues are internalised through habituation, teacher example, and strengthening the Islamic character-based curriculum.strengthening the Islamic character-based curriculum. This research concludes thatIslamic education has a significant contribution in strengthening religiousamid the challenges of modern society. Synergy betweenschool, family, and community so that the process of internalising the values of moderation can run sustainably, so as to create a religious generation.values can run sustainably, thus creating a generation that is religious,inclusive, and adaptive to global dynamics.